Data management platform for citizen science education projects - Angelvik, Nina (UiT Norges arktiske universitet, 2018)
The air:bit project is a computer science education project that we developed in 2016 for use in North-Norwegian upper secondary (videregående) schools. Students build and code their own air quality sensor kits (air:bits), before collecting air quality data in their local areas. They create their own air quality related research questions, which they answer by analyzing the collected air:bit data in context of other air quality data sources. The task of managing such datasets is too complex for such an introductory project and requires a specialized service. This thesis describes the air:bit platform, a scalable and cloud-based data management platform for citizen science education projects. It provides students with a web application for storing, exploring, visualizing and downloading air quality data from air:bits and other data sources. It processes, stores and manages the air:bit data in the Google Cloud Platform, that provides an elastic scaling of storage and computational resources, and in addition simplifies managing the backend. In 2018 the air:bit platform was used by 174 students from 11 school classes across Northern Norway. The students successfully built and programmed 62 air:bits and they uploaded 222 air:bit data log files to the air:bit platform, comprising 481,186 air quality measurements. We demonstrate the air:bit platform's ability to scale with regards to computational resources and that the latency of data uploads and queries is good enough for this purpose. We also provide the cost of processing and storing air:bit data in the cloud. The air:bit platform uses, on average, 30 seconds to verify and insert data log files for one week of per-minute measurements, and less than 2 seconds to process and retrieve the same data for visualization. The total cost of the air:bit platform is $211 per month or $1.20 per student. We believe the air:bit platform is useful not only for the air:bit project, but also for other education projects. It can be used by air quality related citizen science ...